Triticale-oat bread as a new product rich in bioactive and nutrient components. (July 2018) - Fraś, Anna; Gołębiewski, Damian; Gołębiewska, Kinga; Mańkowski, Dariusz R.; Gzowska, Marlena; Boros, Danuta
Abstract: Nowadays non-bread cereals, including oats, due to their healthy properties are increasingly used as additives in bread production. The aim of the present study was to evaluate new healthy triticale-oat bread by replacement as much as possible of triticale flour by high fibre oat concentrate (COF), without decreasing technological quality of bread. The flours obtained from 4 winter triticale varieties were enriched with 2.5%, 5% and 10% of COF. An increasing COF level resulted in significantly increased nutritional parameters content as well as dietary fibre (up to 11.5%), including six-fold increase in β-glucan content (from 0.3% for control breads to 1.0% and 1.8% for 5% and 10% COF, respectively) and as a consequence even two-fold increase in viscosity of water extracts (WEV). Obtained results were compared to popular, available in bakery wheat and wheat-rye breads. All obtained triticale-oat breads can be included as food products high in fibre (over 6 g per 100 g). The dough properties and bread parameters, especially bread volume, shape and crumb texture decreased with the addition of COF. Results show that triticale flour replaced by up to 5% of COF makes it possible to prepare new kind of healthy bread. Highlights: Triticale-oat bread is a new healthy product. Addition of oat fibre increased bioactive properties of triticale bread. Increasing oat fibre content in triticale flour decreased breadmaking quality. Triticale-oat breads are food products high in fibre.